Pancosmorio (world limit) theory of the sustainability of human migration and settlement in space - Irons, Lee G.; Irons, Morgan A. (Frontiers in Astronomy and Space Sciences, 2023)
It seems to be an accepted assumption that human migration into space is inevitable. However, almost 60 years of scientific studies of the effects of space on Earth life suggest this is not a given. Life on Earth evolved in the context of conditions that are unique to Earth and are not duplicated anywhere else in our solar system. The science indicates that life-sustaining conditions on Earth could be the very things that inhibit our ability to live off-Earth. This paper combines 100 years of scientific development of a theory of ecological thermodynamics with classical mechanics theory and analytical models of self-restoring heat engines to explain how the Sun and Earth have evolved into islands of order in the entropy of space. An explanation is provided regarding how naturally occurring conservative force fields engage a diversity of natural resources in semi-reversible cycles that build a high-exergy ecosphere. The science infers that the ability to establish a human settlement in space without Earth-like self-restoring order, capacity, and organization will result in settlement sustainment challenges. Historical evidence of Earth settlements with disrupted ecosystems point to the following possibilities. Supply chains would disappear, market resources would be depleted, advancement in human pursuits would be disrupted, social and governance systems would falter or collapse, human population numbers would decline, genetic diversity in the human genome would be lost, average human individual biomass would decrease, and human knowledge and understanding would be forgotten. What does it mean to have a location in space outside of Earth be “like Earth?” The results of research are presented as a pancosmorio theory ofhuman sustainability that is developed using the scientific philosophy methodology of abductive reasoning. Four analytical models of space ecosphere sustainability and five hypotheses with proposed tests for falsifiability are provided, including a theorem that suggests a limit to human expansion into space. A new quantitative method of human sustainability is developed from theories of network ecology, providing orthogonal properties of an ecosystem network stability function based upon an ecosystem network production function. Conclusions are made regarding the potential for sustainable development in space using balanced sustainability. Insights are provided regarding human endeavors on the Moon and Mars, as well as the Fermi paradox.